The Scientific Research on Environmental Accounting: A Bibliometric Network Analysis - El Alam, Razane; Grande, Umberto; Buonocore, Elvira; Paletto, Alessandro; Franzese, Pier Paolo (Ecological Questions, 2024)
Environmental accounting refers to methodologies aimed at assessing natural resources and the impacts human activities generate on them. Over the past few years, there has been an increasing interest in environmental accounting both in scientific and policy contexts, which recognize its important role in assessing the environmental costs and impacts generated by humans on natural ecosystems. In this study, we explored the global scientific literature on environmental accounting over the last fifty years. Based on scientific publications data, the VOSviewer software was used to generate network maps on environmental accounting displaying the relationships among scientific journals, keywords, researchers, and countries. In total, environmental accounting resulted to be the subject of 1,603 publications. The main keywords related to environmental accounting were “sustainable development”, “environmental economics”, and “sustainability”, highlighting the important role played by environmental accounting tools for assessing environmental sustainability. In addition, United Kingdom, United States, and Italy, resulted the top countries in the research field of environmental accounting. In conclusion, the application of systems thinking in bibliometric science allowed a broad investigation of the research on environmental accounting, resulting a valuable approach for identifying trends and gaps in this research area.